A literatura veiculada pela campanha da fraternidade: Significação e Cultura - Almeida, Thiago da Silva (2021)
This thesis aims to analyze, from a semiotic point of view, the cultural meanings present in literary texts conveyed by the Fraternity Campaign, whose celebration has undergone reformulations with regard to the direction of its choices since its first edition in the sixties. At first, the Church focused on renewing its internal structure. Then, he started to worry about the social reality of the people, but still doing it internally. Finally, the Church becomes interested in the existential issues of the Brazilian people, but acting in a more proactive and participatory way in society. It is in this third moment that the present work delimits its focus, specifically from 1985, when the Brazilian military regime ended, until the first decade of the 21st century. The methodological proposal employed, of an interpretative and comparative nature, uses as hymns corpus which are verbal texts in generally appealing language and posters, syncretic texts that unite the verbal to the imagetic. These are analyzed with the theoretical basis of the Semiotics of Cultures of the French line, mainly the contributions of semioticians François Rastier (2010) and Teodoro Pais (2009). Conceived as a science for the interpretation of cultural meanings, it comprises the shared knowledge, worldview and value systems of a sociocultural group as an integral part of a social identity. The work is delimited in three moments: theoretical studies on the basic foundations of semiotics cultures, followed by an overview of the main semiotic trends, such as the North American, the Russian and the French. In sequence, a brief history of the Fraternity Campaign was made, with information about the first celebrations. Finally, the analytical work of the corpus was carried out, which showed a culture centered on the inclusion and acceptance of differences.